Rancang Bangun Aplikasi Pelaporan Keadaan Darurat di Kota Mataram(Studi Kasus Nomor Panggilan Darurat 112) - I Made Dwi Mahardika; Royana Afwani; Moh. Ali Albar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2020)
Emergencies can occur anywhere and anytime, where handling these emergencies must be done quickly. This research was conducted to design and build an emergency reporting system in the city of Mataram. The emergency reporting system that was built took the workflow from the emergency call number 112. The system will be used by 4 users namely the citizen as a emergency reporter, call taker emergency call number 112 from Diskominfo as an information processor, admin as a call taker information processor and units such as ambulances and firefighters as the action takers of the submitted report. The system runs in 2 platforms, namely the web pages used by call takers and Android, which are used by the public and action units. The system is tested using the mean opinion score and black box testing. The results obtained by using the mean opinion score test is 3.6 or the fair category.